Methodology for assessing rice varieties for resistance to the lesser grain borer, Rhyzopertha dominica - Y. Chanbang (2018)
Several physical and chemical attributes of rice were evaluated to determine which character would be best to use to assess multiple rice varieties for resistance to the lesser grain borer, Rhyzopertha dominica (F.). Laboratory tests were conducted on single varieties of long-, short-, and medium grain-rice to develop procedures and methodologies that could be used for large-scale screening studies. Progeny production of R. dominica was positively correlated with the percentage of broken hulls. Although kernel hardness, amylose content, neonate preference for brown rice, and adult emergence from neonates varied among the three rice varieties tested they did not appear to be valid indicators of eventual progeny production, and may not be useful predictors of resistance or susceptibility. Soundness and integrity seem to be the best characters to use for varietal screening studies with R. dominica.